1993
DOI: 10.1148/radiology.189.2.8210392
|View full text |Cite
|
Sign up to set email alerts
|

Solid breast lesions: diagnosis with US-guided fine-needle aspiration biopsy.

Abstract: Real-time US-guided fine-needle aspiration biopsy is a useful adjunct to clinical, mammographic, and sonographic assessment of solid breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 0 publications
4
37
1
3
Order By: Relevance
“…When the inadequate cases were excluded from the calculations, the accuracy of FNAC was falsely increased. 13 We obtained a nondiagnostic sample rate of 14% with FNAC. This is below the accepted limit of 20%, but is above 10% reported with experienced operators.…”
Section: Discussionmentioning
confidence: 99%
“…When the inadequate cases were excluded from the calculations, the accuracy of FNAC was falsely increased. 13 We obtained a nondiagnostic sample rate of 14% with FNAC. This is below the accepted limit of 20%, but is above 10% reported with experienced operators.…”
Section: Discussionmentioning
confidence: 99%
“…7 A more-complex and time consuming (30-60 minutes) cytologic assay is the well-established Papanicolaou staining, which is currently used for the assessment of fine needle aspiration cytology (FNAC) of breast lesions. 8,9 We directly compared Diff-Quik and Papanicolaou staining of ultrasound-guided CNB specimens for their diagnostic value.…”
Section: Objective: To Investigate Whether Imprint Cytology Of Core Nmentioning
confidence: 99%
“…In the present study, we showed that this technique is useful and sensitive for the diagnosis and management of small and nonpalpable breast masses. A few investigators have reported on the accuracy and clinical usefulness of this technique [16][17][18]. However, previous studies did not describe the management of breast masses and staging of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FNAB under US guidance was first reported in 1987 [15]. There are few reports, however, on the usefulness of FNAB under US guidance [16][17][18] and there has been no report of clinical management of nonpalpable or small mases based on FNAB under US guidance.…”
Section: Introductionmentioning
confidence: 99%